RELEVANSI PEMIKIRAN IBNU TAIMIYYAH TERHADAP KONSEP PENDIDIKAN HOLISTIK DALAM PENDIDIKAN ISLAM KONTEMPORER - Ahwani, Muhamad Alfan; Hasiolan; Kadiyo (Prodi Magister Pendidikan Agama Islam (MPAI) - STAI Nida El-Adabi Bogor, 2025)
Ibn Taymiyya’s intellectual contributions have played a pivotal role in shaping the concept of holistic education within Islam, particularly in the framework of contemporary Islamic pedagogy. This study aims to explore how his ideas can inform and enhance educational models that integrate intellectual, spiritual, and moral dimensions. Employing a qualitative methodology with a library research approach, the study critically examines Ibn Taymiyya’s works on education and evaluates their relevance to modern educational practices. The findings indicate that his thought advocates for the synthesis of revealed knowledge and rational inquiry, positioning the principle of monotheism as the foundational basis for cultivating a resilient Muslim character. Moreover, his emphasis on ethics and practical moral engagement aligns closely with holistic educational principles, which seek to balance cognitive, affective, and psychomotor development. Consequently, Ibn Taymiyya’s educational philosophy can serve as a strategic reference for designing Islamic education systems that uphold core religious values while addressing contemporary societal challenges.